Adalimumab in the treatment of cardiac sarcoidosis: Single center case series and narrative literature review. (2022) - Sweis, Jaleel Jerry G.; Sweis, Nabil William G.; Ascoli, Christian; Levin, Benjamin; Avitall, Boaz; Rubinstein, Israel; Kondos, George; Culver, Daniel A.; Judson, Marc; Baughman, Robert; Darbar, Dawood; Drake, Wonder; et al.
Abstract: Background: Tumor necrosis factor (TNF) inhibitors have been used in the treatment of cardiac sarcoidosis, infliximab being the most commonly used. We have previously reported a case of effective treatment of cardiac sarcoidosis using adalimumab. Objective: To describe our experience of using adalimumab in the treatment of cardiac sarcoidosis. Methods: We conducted a retrospective study to evaluate patients with cardiac sarcoidosis who received adalimumab treatment at the University of Illinois Health between 2011 and 2022. The outcome was evaluated by assessing safety, tolerability, and ability to taper systemic corticosteroids therapy following initiation of adalimumab. Results: Seven patients met the inclusion criteria. Clinical responses to adalimumab were universally positive. Corticosteroid therapy was discontinued in five patients and the dose was reduced in two patients. Furthermore, adalimumab was well tolerated, and no adverse events were reported. Conclusion: Adalimumab was safe and well-tolerated in seven patients with cardiac sarcoidosis seen at our medical center and exhibited corticosteroid-sparing effects. Our observation further warrants large prospective studies to evaluate the safety and efficacy of adalimumab in the treatment of cardiac sarcoidosis.